1986
DOI: 10.1093/ptj/66.8.1233
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Rehabilitation

Abstract: The purpose of this study was to compare the therapeutic efficacy of three exercise therapy approaches. Three groups of adult stroke patients (N = 131) participated in the study. The first group received conventional treatment that consisted of traditional exercises and functional activities. The treatment of the second group was based on proprioceptive neuromuscular facilitation techniques. The third group was treated using the Bobath approach. The improvement of each patient was evaluated after six weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…This currently under-represented aspect will need to be appreciated more thoroughly within an interdisciplinary concept of stroke rehabilitation. Certainly, physical activity in the form of exercise rehabilitation belongs to the standard therapy after stroke [31], prevention or restoring of muscle metabolic abnormalities will substantially contribute to this. Thus, a clinical study in older acute stroke patients revealed that nutritional supplementation within the first week in hospital has a beneficial effect for maintaining an adequate body mass and body composition [32].…”
Section: Muscle Wasting In Stroke—not Appreciated In the Guidelinesmentioning
confidence: 99%
“…This currently under-represented aspect will need to be appreciated more thoroughly within an interdisciplinary concept of stroke rehabilitation. Certainly, physical activity in the form of exercise rehabilitation belongs to the standard therapy after stroke [31], prevention or restoring of muscle metabolic abnormalities will substantially contribute to this. Thus, a clinical study in older acute stroke patients revealed that nutritional supplementation within the first week in hospital has a beneficial effect for maintaining an adequate body mass and body composition [32].…”
Section: Muscle Wasting In Stroke—not Appreciated In the Guidelinesmentioning
confidence: 99%
“…Yet interestingly, conventional treatment regimens based on an unspecific peripheral modulation of motor tone can lead to neurofunctional change [106]. Nonetheless, clinical effects remain insubstantial, independent of the time of treatment onset, be it early on [107] or in later stages of recovery [108]. On the other hand, if interventions are more closely related to the ‘relearning’ of motor functions, a certain superiority to traditional schemes is seen [109].…”
Section: Effects Of Stroke Rehabilitation In Humansmentioning
confidence: 99%
“…Follow-up periods have ranged from one week (Lindenberg et al, 2010; Nair et al, 2011) to three months (Khedr et al, 2013). As a result, numerous questions exist regarding the role of tDCS as an adjunct to PT over the course of an entire plan of care, which for UE PT, typically includes approximately 960 minutes dispersed over 24 treatment sessions (Birkenmeier, Prager, & Lang, 2010; Chang, Tung, Wu, Huang, & Su, 2007; Dickstein, Hocherman, Pillar, & Shaham, 1986; Kimberley, Samargia, Moore, Shakya, & Lang, 2010; Lang, MacDonald, & Gnip, 2007; Wang, Zhao, Zhu, Li, & Meng, 2011). Is providing stimulation throughout an entire plan of care feasible?…”
Section: Introductionmentioning
confidence: 99%